Applicability of 4D modeling for resource allocation in mega liquefied natural gas plant construction - Zhou, Y.; Ding, L.; Wang, Xiangyu; Truijens, M.; Luo, H. (Elsevier, 2015)
Four-dimensional (4D) modeling has gained much potential in improving construction process design and planning. The integration of three-dimensional model with scheduling information has been shown to enable the effective detection of construction process design and planning flaws. However, the research work in 4D has been predominantly focused on the building construction industry. 4D has been rarely explored in the oil and gas industry, particularly Liquefied Natural Gas (LNG) plant construction. It is very difficult to conceive the scale and complexity of mega-projects in the LNG sector. This paper presents a study with the goal of investigating the feasibility and benefits of 4D in supporting LNG construction projects. 4D models were developed at both the activity level and the operations level, and geometry-based virtual construction was implemented to rehearse the construction process for the purpose of identifying potential risks and safety issues. These models were used for synergistic planning for the whole project and for resource scheduling. It has been demonstrated in this paper, mega LNG construction projects can benefit from 4D in terms of improved process planning and control.